Trend and Trajectory of Islamic Finance for Sustainable Development Planning (Ekonomi Syariah IAIN Kudus, 2024)
This study investigates the role of Islamic Wealth Management (IWM) and sharia financial planning in achieving sustainable development through bibliometric analysis. The research utilizes data from academic databases, focusing on publications from 2020-2024, and employs VOSviewer to visualize trends and relationships among key concepts. The literature review includes critical themes, including the integration of fintech and blockchain technologies with Islamic finance to enhance transparency, financial inclusion, and sustainability. Findings highlight the significant potential of Islamic financial instruments, such as zakat, waqf, and green sukuk, in addressing global challenges like poverty alleviation and environmental protection, aligning with the Sustainable Development Goals (SDGs) and maqasid al-sharia. However, challenges persist, including regulatory gaps, the complexity of financial products, and the need for robust sharia governance frameworks. This study underscores the transformative potential of digital innovations in Islamic finance to create inclusive and ethical financial systems while emphasizing the necessity of regulatory and institutional support for broader implementation.